Effect of Administration of Lignocellulose-Degrading Fungi Isolated from Herbivoreâs Gastrointestinal Tract for Fiber Degradation - Wahyudi, A; Cahyanto, MN; Soejono, M; Bachruddin, Z (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
Isolation and selection of lignocellulose-degrading fungi from compartment of herbivoreâs gastrointestinal tract were predicted found fungi that have superiority to degrade lignin, xylan, and cellulose. Lignocellulose-degrading fungi were isolated from compartment of buffaloâs and horseâs gastrointestinal tract andÂ also elephant dung with malt extract agar, using cellulose, xylan, and tannic acid as selective substrate. Morphological and biochemical test had been done to get superior isolates. This study showed that lignocellulose-degrading fungi could be found in all sample of buffaloâs and horseâs gastrointestinal tract and also elephant dung. The highest number of lignin, xylan and cellulose-degrading isolates respectively were found from buffaloâs cecum (5 isolates), buffaloâs colon (19 isolates), and buffaloâs colon (326 isolates). The highest isolates activity of lignolytic, xylanolytic, and cellulolytic respectively were reached from horseâs cecum (2.38), horses cecum (6.67), and buffaloâs colon (5.60). Meanwhile the highest enzymes activities were reached from horseâs cecum (0.166 Unit/g protein), horseâs cecum (5.037 Unit/g protein) and buffaloâs colon (2.488 Unit/g protein). From this study could be concluded that lignocellulose-degrading fungi could be found from all compartment of herbivoreâs gastrointestinal tract. Based on quantitative and qualitative selection, lignolytic from horseâs cecum, xylanolytic from horseâs cecum and cellulolytic from buffaloâs colon were superior isolates and predicted as Aspergillus sp genus. Administratiton of Aspergilillus sp inoculum into rumen fluid medium elevated significantly dry matter, organic matter,Â crude fiber, neutral detergent fiber, and acid detergent fiber digestibility as 4.55%; 4.45%; 6.69%; 11.65% and 8.23% respectively. (Animal Production 12(1): 21-28 (2010)Key Words : lignocellulose-degrading fungi, herbivoreâs gastrointestinal tract, fiber degradation.